2004
DOI: 10.1113/jphysiol.2004.069302
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐pulmonary shunt and pulmonary gas exchange during exercise in humans

Abstract: In young, healthy people the alveolar-arterial P O 2 difference (A-aDO 2 ) is small at rest, but frequently increases during exercise. Previously, investigators have focused on ventilation/perfusion mismatch and diffusion abnormalities to explain the impairment in gas exchange, as significant physiological intra-pulmonary shunt has not been found. The aim of this study was to use a non-gas exchange method to determine if anatomical intra-pulmonary (I-P) shunts develop during exercise, and, if so, whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
196
6
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(218 citation statements)
references
References 46 publications
12
196
6
4
Order By: Relevance
“…A disadvantage is that it can be difficult to image a patient during exercise in this position if they have abdominal obesity. To date, similar results have been found when comparing right-to-left shunt during recumbent and upright exercise (Stickland et al, 2004;La Gerche et al, 2010;Elliott et al, 2011a). There are no published data examining intrapulmonary shunting during supine exercise.…”
Section: Detection Of Intracardiac and Intrapulmonary Shunts At Restsupporting
confidence: 65%
See 2 more Smart Citations
“…A disadvantage is that it can be difficult to image a patient during exercise in this position if they have abdominal obesity. To date, similar results have been found when comparing right-to-left shunt during recumbent and upright exercise (Stickland et al, 2004;La Gerche et al, 2010;Elliott et al, 2011a). There are no published data examining intrapulmonary shunting during supine exercise.…”
Section: Detection Of Intracardiac and Intrapulmonary Shunts At Restsupporting
confidence: 65%
“…In a research setting, subjects can be in a supine, upright or reclined position, however interpretation of the echocardiograms should take into account body positioning during ultrasound imaging. Specifically, there are data suggesting that intrapulmonary arteriovenous anastomoses are patent in the supine position, but not in the upright position (Stickland et al, 2004;Elliott et al, 2011b). Also, Tobin & Zariquiey demonstrated that intrapulmonary arteriovenous anastomoses 20 to 500 m in functional diameter are located in the apex of the human lung (Tobin & Zariquiey, 1950).…”
Section: Intrapulmonary Shuntsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body positioning can be a factor in recruitment of these transpulmonary pathways, especially in the supine position. 8 Therefore, changing the patient's position from sitting to supine during an interventional procedure under increased pulmonary microvasculature pressure, i.e., when significant venous air emboli are present, may increase the risk for transpulmonary transmission, especially via pathways in the apical lung.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] While these physiological transpulmonary arteriovenous pathways are subclinical in most instances, they have potential to open in up to 90% of individuals during hyperdynamic situations such as exercise. [8][9][10] A recent review of pulmonary pathways and mechanisms pertaining to their autoregulation highlights the interest and importance of this subject. 11 Neuroanesthesiologists are well aware of the multiple pathways for paradoxical air embolism (PAE) to occur.…”
Section: Résumémentioning
confidence: 99%